Biodegradability and Cytocompatibility of 3D-Printed Mg-Ti Interpenetrating Phase Composites - Yang, Xixiang; Huang, Wanyi; Zhan, Desong; Ren, Dechun; Ji, Haibin; Liu, Zengqian; Wang, Qiang; Zhang, Ning; Zhang, Zhefeng (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Orthopedic hybrid implants combining both Titanium (Ti) and Magnesium (Mg) are nowadays becoming increasingly attractive. However, there remains a huge challenge in the fabrication of Mg-Ti composite due to the higher melting point of Ti than the volatilization temperature of pure Mg. Here, we successfully fabricated a new Mg-Ti composite with a bi-continuous interpenetrating-phase architecture by infiltrating Mg melt into Ti scaffolds, which was prepared for 3D printing and subsequent acid treatment. In this study, an attempt was made to understand the effects of the Mg-Ti composite during the 7-day degradation, as well as to examine the impact on the MC3T3-E1 cells by varying Mg2+ concentrations, such as toxicity, morphology, apoptosis and osteogenic activity. CCK-8 results indicated cytotoxicity absence of Mg-Ti composite during 7-day degradation. Moreover, the composite significantly improved the morphology, reduced the apoptosis rate and enhanced the osteogenic activity of MC3T3-E1 cells. The favorable impacts might be attributed to the appropriate Mg2+ concentration of the extracts. The results on varying Mg2+ concentration test indicated that Mg2+ showed no adverse effect to cells under 10 mM concentration. The 8 mM group exhibited the best cell morphology, minimum apoptosis rate and maximum osteogenic activity. This work may open a new perspective on the development and biomedical applications for Mg-Ti composites.